Use Of Learning Technology (E-Learning) At Mtsn 3 South Bengkulu: Challenges and Opportunities - Sugianto, Ii; Insanistyo, Bayu (CV Media Inti Teknologi, 2025)
Abstract:Background of Study The Ministry of Religious Affairs of the Republic of Indonesia has developed an E-Learning platform to advance educational technology and promote the digitalization of learning in madrasahs. Madrasah Tsanawiyah Negeri (MTsN) 3 South Bengkulu has adopted this system; however, its implementation has not yet reached an optimal level due to various infrastructural and pedagogical challenges. Aims and Scope This study investigates the challenges and opportunities associated with the use of E-Learning at MTsN 3 South Bengkulu, with a specific focus on its application in conducting learning evaluations. The scope encompasses identifying barriers, evaluating institutional readiness, and proposing feasible strategies for improvement. MethodsA descriptive research design was employed, integrating qualitative and quantitative approaches. Data were collected through observations, interviews, and questionnaires, and analyzed using data triangulation to ensure validity and reliability. ResultsThe study identified several obstacles to effective E-Learning implementation: limited access to digital devices, unstable internet connectivity, inadequate technological readiness among teachers and students, low student motivation, insufficient understanding of online learning, unsupportive home learning environments, and a lack of parental support in providing technological resources. Opportunities include enhancing digital literacy, integrating interactive learning activities, and strengthening stakeholder collaboration. ConclusionSuccessful E-Learning implementation in madrasahs requires coordinated efforts among government bodies, educational institutions, and private stakeholders. Recommendations include expanding device access, providing targeted digital literacy training, and designing engaging online learning strategies to optimize both instructional delivery and evaluation processes.